Forgotten Witnesses: The Illustrations of Ms Escorial, I.I.3 and the Dispute over the Biblias Romanceadas - Porto, Rosa M. Rodríguez (Medieval encounters, 2018)
This article offers a preliminary survey of the miniatures illustrating the Biblia romanceada held at the Escorial Library under the shelf number I.I.3, whose precise date and provenance have been a matter of dispute among scholars for decades. The scrutiny of the stylistic features of these illustrations together with a reassessment of the scarce archival sources related to this work allows for a definite association of Escorial, MS I.I.3 with Enrique de Guzmán, 2nd Duke of Medina Sidonia (d. 1492). However, the contextualized analysis of this lavishly decorated manuscript—which was part of a trend in aristocratic patronage and the epitome of already established traditions in Bible illustration—may contribute not only to a re-appraisal of this singular work but also to a better understanding of the multifaceted phenomena lying behind the production and reception of the remaining fifteenth-century illustrated Bibles in the vernacular, all of them translated from Hebrew but intended for a Christian audience.